Hydrogen permeation resistant protective layer capable of prolonging service life of titanium alloy and preparation method of hydrogen permeation resistant protective layer

By forming a hydrogen permeability protection layer of Al2O3 and TiO2 on the surface of the titanium alloy, the problem of hydrogen permeability of titanium alloy in a hydrogen environment is solved, and its fatigue life and service life are significantly improved.

CN119824360AActive Publication Date: 2025-04-15XIAN UNIV OF TECH

Patent Information

Application Number
CN202411946012.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-15
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

Titanium alloys are prone to hydrogen permeation in hydrogen environments, resulting in a decrease in strength, plasticity and fatigue properties, affecting their service reliability.

Method used

Different proportions of oxygen and argon are used for oxygen permeation treatment, and a hydrogen-retardant protective layer of outer layer Al2O3 and inner layer TiO2 is formed on the surface of the titanium alloy. Insoluble hydride is formed by combining Ti and Al elements with hydrogen, thereby hindering the diffusion and aggregation of hydrogen.

Benefits of technology

It significantly improves the fatigue life of titanium alloy in hydrogen environment, extends its service life, while reducing production costs and improving production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824360A_ABST
    Figure CN119824360A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a hydrogen permeation resistant protective layer capable of prolonging the service life of titanium alloy, which specifically comprises the following steps: step 1, accurately mixing oxygen and argon through a mixing device according to a set proportion; 2, a titanium alloy matrix containing the aluminum element is selected; 3, the titanium alloy selected in the step 2 is subjected to ultrasonic cleaning and then loaded into a vacuum furnace, argon is introduced, a vacuum pump vacuumizes to 8 Pa, then the temperature of the vacuum furnace is increased to the oxygen permeation temperature, the vacuum pump is closed after 1.5 h, finally, the gas mixed in the step 1 is introduced into the vacuum furnace, the oxygen permeation process is conducted, and the hydrogen permeation resisting protective layer is prepared on the surface of the titanium alloy; the outer layer of the prepared hydrogen permeation preventing protective layer is Al2O3, the inner layer of the prepared hydrogen permeation preventing protective layer is TiO2, the hydrogen permeation preventing protective layer can prevent hydrogen atoms from permeating into the titanium alloy, and the bending fatigue life of the titanium alloy is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal material surface protection, and in particular relates to a hydrogen permeation-resistant protective layer for improving the service life of a titanium alloy and a preparation method thereof. Background Art

[0002] The density of titanium alloy is about 60% of that of steel, and it has a high specific strength, which makes it suitable for manufacturing parts with high strength and good rigidity. However, hydrogen atoms have a small radius and a high diffusion rate in the crystal lattice. They are particularly prone to aggregation along crystal dislocations and interfaces to generate brittle hydrides, which leads to a sudden decrease in the strength, plasticity, toughness and fatigue properties of titanium alloys, endangering the service reliability of the structural parts prepared from them.

[0003] The vacant hydrogen traps, micro-nanopores and hydrogen in the Al2O3 structure generate water and aluminum oxide compounds that hinder the movement of hydrogen molecules, effectively hinder the diffusion of hydrogen, and slow down the penetration rate of hydrogen. At the same time, hydrogen atoms tend to occupy the octahedral interstitial positions of TiO2 oxygen atoms and form OH bonds with the nearest oxygen atoms. Therefore, the surface oxide layer with Al2O3 as the outer layer and TiO2 as the inner layer can effectively hinder the penetration of hydrogen into the matrix, and the Ti atoms doped into the aluminum oxide at the interface can form insoluble stable hydride TiH by combining with hydrogen to hinder the diffusion and aggregation of hydrogen, thereby improving the material's resistance to hydrogen permeation. Summary of the invention

[0004] The purpose of the present invention is to provide a hydrogen permeation resistance protective layer for improving the service life of titanium alloy and a preparation method thereof. The hydrogen permeation resistance protective layer can improve the fatigue life of titanium alloy under hydrogen environment service.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] A method for preparing a hydrogen permeation-resistant protective layer for improving the service life of a titanium alloy comprises the following steps:

[0007] Step 1, mixed gas: turn on the gas source, let oxygen and argon pass through the mixing device in the set ratio to achieve precise mixing, and use the sensor to monitor the concentration of the mixed gas. The argon concentration is 99.999% and the oxygen concentration is 99.5%;

[0008] Step 2, titanium alloy selection: the titanium alloy matrix needs to contain aluminum elements, and a new metastable β titanium alloy is selected, whose nominal composition is Ti3Al15V3Cr3Sn;

[0009] Step 3, preparation of a hydrogen permeation resistance protective layer: the titanium alloy selected in step 2 is ultrasonically cleaned and then loaded into a vacuum furnace. First, argon gas is introduced and the vacuum pump is evacuated to 8Pa. Then the temperature of the vacuum furnace is increased to the oxygen permeation temperature. After 1.5 hours, the vacuum pump is turned off. Finally, the mixed gas in step 1 is introduced into the vacuum furnace. The pressure in the vacuum furnace is 0.023MPa. At this time, the pressure in the vacuum furnace is lower than the standard atmospheric pressure. The oxygen permeation process is carried out to prepare a hydrogen permeation resistance protective layer on the surface of the titanium alloy.

[0010] Furthermore, in step 1, the contents of oxygen and argon are: 80-95% argon and 5%-20% oxygen.

[0011] Furthermore, in step 2, the hydrogen content of the titanium alloy is less than 5 PPm.

[0012] Furthermore, in step 3, the oxygenation temperature is 300-600° C., and the oxygenation process lasts 1-24 hours.

[0013] The hydrogen permeation barrier layer prepared according to the above-mentioned method for preparing a hydrogen permeation barrier layer for improving the service life of titanium alloy has an outer layer of Al2O3 and an inner layer of TiO2. The Ti and Al elements in the hydrogen permeation barrier layer come from the inside of the titanium alloy, and the O element comes from the mixed gas of oxygen and argon in the vacuum furnace.

[0014] Compared with the prior art, the present invention has the following beneficial effects:

[0015] The present invention provides a method for preparing a hydrogen permeation resistance protective layer for improving the service life of a titanium alloy. Different mixed oxygen and argon gases are used as oxygen permeation conditions, and the hydrogen permeation resistance protective layer is diffused in situ in a titanium alloy matrix. No titanium and aluminum alloy elements need to be added, and the cost is low. The product production efficiency is high. The prepared hydrogen permeation resistance protective layer is evenly distributed and has good plasticity. It meets the bending fatigue behavior of the alloy without cracking, and has the function of hindering the diffusion and penetration of hydrogen. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is a morphology diagram of the hydrogen permeation barrier layer and the titanium alloy substrate prepared in Example 1 of the present invention;

[0017] Figure 2 This is a morphology diagram of an oxide having a hydrogen permeation-resistant protective layer prepared in Example 4 of the present invention. DETAILED DESCRIPTION

[0018] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0019] A method for preparing a hydrogen permeation-resistant protective layer for improving the service life of a titanium alloy comprises the following steps:

[0020] Step 1, mixed gas: turn on the gas source, let oxygen and argon pass through the mixing device in the set ratio to achieve precise mixing. The content of oxygen and argon is: 80-95% argon, 5%-20% oxygen. Use a sensor to monitor the concentration of the mixed gas, the argon concentration is 99.999%, and the oxygen concentration is 99.5%;

[0021] Step 2, titanium alloy selection: the titanium alloy matrix needs to contain aluminum elements, and a new metastable β titanium alloy is selected, whose nominal composition is Ti3Al15V3Cr3Sn, and the hydrogen content of the titanium alloy is less than 5PPm;

[0022] Step 3, preparation of a hydrogen permeation resistance protective layer: the titanium alloy selected in step 2 is ultrasonically cleaned and then loaded into a vacuum furnace. In order to effectively reduce the content of oxygen and water vapor in the furnace, argon gas is first introduced and the vacuum pump is evacuated to 8 Pa. The temperature of the vacuum furnace is then increased to an oxygen permeation temperature of 300-600°C. After 1.5 hours, the vacuum pump is turned off. Finally, the mixed gas prepared in step 1 is introduced into the vacuum furnace. The vacuum pressure gauge accurately shows that the pressure value inside the system is 0.023 MPa. At this time, the pressure in the vacuum furnace is lower than the standard atmospheric pressure. The oxygen permeation process is carried out for 1-24 hours to prepare a hydrogen permeation resistance protective layer on the surface of the titanium alloy.

[0023] The hydrogen permeation barrier layer prepared according to the above-mentioned method for preparing a hydrogen permeation barrier layer for improving the service life of titanium alloy has an outer layer of Al2O3 and an inner layer of TiO2. The Ti and Al elements in the hydrogen permeation barrier layer come from the inside of the titanium alloy, and the O element comes from the mixed gas of oxygen and argon in the vacuum furnace.

[0024] The reasons and functions of the two oxide layers in the hydrogen permeation barrier are as follows:

[0025] 1. The vacant hydrogen traps, micro-nano pores and hydrogen reactions in the alumina structure generate water and alumina compounds that hinder the movement of hydrogen molecules, effectively hinder the diffusion of hydrogen and slow down the penetration rate of hydrogen to meet the needs of different applications.

[0026] 2. Hydrogen atoms easily occupy the octahedral interstitial positions of TiO2 oxygen atoms and form OH bonds with the nearest oxygen atoms.

[0027] 3. Ti atoms doped into alumina at the interface can combine with hydrogen to form insoluble stable hydride TiH to hinder the diffusion and aggregation of hydrogen, thereby improving the hydrogen resistance of the material.

[0028] Example 1

[0029] A method for preparing a hydrogen permeation-resistant protective layer for improving the service life of a titanium alloy, the specific steps are as follows:

[0030] Step 1, mixed gas: turn on the gas source and let oxygen and argon pass through the mixing device in the set ratio to achieve precise mixing. The content of oxygen and argon is: 80% argon and 20% oxygen. Use a sensor to monitor the concentration of the mixed gas. The argon concentration is 99.999% and the oxygen concentration is 99.5%.

[0031] Step 2, titanium alloy selection: The titanium alloy matrix needs to contain aluminum elements. A new metastable β titanium alloy is selected, whose nominal composition is Ti3Al15V3Cr3Sn. The hydrogen content of the titanium alloy before oxidation is less than 5PPm.

[0032] Step 3, preparation of a hydrogen permeation resistance protective layer: the titanium alloy selected in step 2 is ultrasonically cleaned and then loaded into a vacuum furnace. In order to effectively reduce the content of oxygen and water vapor in the furnace, argon gas is first introduced and the vacuum pump is evacuated to 8 Pa. The temperature of the vacuum furnace is then increased to the oxygen permeation temperature of 350°C. After 1.5 hours, the vacuum pump is turned off. Finally, the mixed gas in step 1 is introduced into the vacuum furnace. The vacuum pressure gauge accurately shows that the pressure value inside the system is 0.023 MPa. At this time, the pressure in the vacuum furnace is lower than the standard atmospheric pressure. The oxygen permeation process is carried out for 6 hours to prepare a hydrogen permeation resistance protective layer on the surface of the titanium alloy.

[0033] The titanium alloy with a hydrogen permeation barrier layer prepared in this embodiment was subjected to a hydrogen permeation experiment using an electrochemical workstation. The hydrogen permeation time was 7 days. All electrolytic solutions were 3.5% NaCl aqueous solutions. The negative electrode was the titanium alloy with a hydrogen permeation barrier layer, the positive electrode was pure zinc, and the temperature was room temperature.

[0034] The titanium alloy with the hydrogen permeation barrier layer prepared in this embodiment was tested using a homemade bending fatigue testing machine to obtain the life before fracture under room temperature conditions. A 45° bending fatigue test was performed on a QJWQ-6 CNC bending testing machine at a rate of 60 times per minute until the sample fractured, and the bending fatigue life was obtained.

[0035] The hydrogen permeation barrier layer for improving the life of titanium alloy prepared by in-situ oxidation method in Example 1 has a microstructure morphology as shown in FIG. Figure 1 The hydrogen permeation barrier layer and the titanium alloy substrate are well bonded, and there is no crack between the hydrogen permeation barrier layers. After bending fatigue testing, the bending life before fracture is 1.2 x 10 4 , which is 1.79 times the fatigue life of the titanium alloy without a hydrogen permeation barrier (the initial fatigue life of the titanium alloy without a hydrogen permeation barrier is 6704 times).

[0036] Example 2

[0037] A method for preparing a hydrogen permeation-resistant protective layer for improving the service life of a titanium alloy, the specific steps are as follows:

[0038] Step 1, mixed gas: turn on the gas source and let oxygen and argon pass through the mixing device in the set ratio to achieve precise mixing. The content of oxygen and argon is: 85% argon and 15% oxygen. Use a sensor to monitor the concentration of the mixed gas. The argon concentration is 99.999% and the oxygen concentration is 99.5%.

[0039] Step 2, titanium alloy selection: The titanium alloy matrix needs to contain aluminum elements. A new metastable β titanium alloy is selected, whose nominal composition is Ti3Al15V3Cr3Sn. The hydrogen content of the titanium alloy before oxidation is less than 5PPm.

[0040] Step 3, preparation of a hydrogen permeation resistance protective layer: the titanium alloy selected in step 2 is ultrasonically cleaned and then loaded into a vacuum furnace. In order to effectively reduce the content of oxygen and water vapor in the furnace, argon gas is first introduced and the vacuum pump is evacuated to 8 Pa. The temperature of the vacuum furnace is then increased to the oxygen permeation temperature of 350°C. After 1.5 hours, the vacuum pump is turned off. Finally, the mixed gas in step 1 is introduced into the vacuum furnace. The vacuum pressure gauge accurately shows that the pressure value inside the system is 0.023 MPa. At this time, the pressure in the vacuum furnace is lower than the standard atmospheric pressure. The oxygen permeation process is carried out for 12 hours to prepare a hydrogen permeation resistance protective layer on the surface of the titanium alloy.

[0041] The titanium alloy with a hydrogen permeation barrier layer prepared in this embodiment was subjected to a hydrogen permeation experiment using an electrochemical workstation. The hydrogen permeation time was 7 days. All electrolytic solutions were 3.5% NaCl aqueous solutions. The negative electrode was the titanium alloy with a hydrogen permeation barrier layer, the positive electrode was pure zinc, and the temperature was room temperature.

[0042] The titanium alloy with the hydrogen permeation barrier layer prepared in this embodiment was tested using a homemade bending fatigue testing machine to obtain the life before fracture at room temperature. A 45° bending fatigue test was performed on a QJWQ-6 CNC bending testing machine at a rate of 60 times per minute until the sample fractured, and the bending fatigue life was obtained.

[0043] The hydrogen permeation barrier layer for improving the life of titanium alloy prepared by in-situ oxidation in Example 2 has a bending fatigue test and a bending life of 3.0 x 10 4 , which is 4.47 times the fatigue life of the titanium alloy without a hydrogen permeation barrier (the initial titanium alloy without a hydrogen permeation barrier is 6704 times).

[0044] Example 3

[0045] A method for preparing a hydrogen permeation-resistant protective layer for improving the service life of a titanium alloy, the specific steps are as follows:

[0046] Step 1, mixed gas: turn on the gas source and let oxygen and argon pass through the mixing device in the set ratio to achieve precise mixing. The content of oxygen and argon is: 95% argon and 5% oxygen. Use a sensor to monitor the concentration of the mixed gas. The argon concentration is 99.999% and the oxygen concentration is 99.5%.

[0047] Step 2, titanium alloy selection: The titanium alloy matrix needs to contain aluminum elements. A new metastable β titanium alloy is selected, whose nominal composition is Ti3Al15V3Cr3Sn. The hydrogen content of the titanium alloy before oxidation is less than 5PPm.

[0048] Step 3, preparation of a hydrogen permeation resistance protective layer: the titanium alloy selected in step 2 is ultrasonically cleaned and then loaded into a vacuum furnace. In order to effectively reduce the content of oxygen and water vapor in the furnace, argon gas is first introduced and the vacuum pump is evacuated to 8 Pa. The temperature of the vacuum furnace is then increased to the oxygen permeation temperature of 300°C. After 1.5 hours, the vacuum pump is turned off. Finally, the mixed gas in step 1 is introduced into the vacuum furnace. The vacuum pressure gauge accurately shows that the pressure value inside the system is 0.023 MPa. At this time, the pressure in the vacuum furnace is lower than the standard atmospheric pressure. The oxygen permeation process is carried out for 18 hours to prepare a hydrogen permeation resistance protective layer on the surface of the titanium alloy.

[0049] The titanium alloy with a hydrogen permeation barrier layer prepared in this embodiment was subjected to a hydrogen permeation experiment using an electrochemical workstation. The hydrogen permeation time was 7 days. All electrolytic solutions were 3.5% NaCl aqueous solutions. The negative electrode was the titanium alloy with a hydrogen permeation barrier layer, the positive electrode was pure zinc, and the temperature was room temperature.

[0050] The titanium alloy with the hydrogen permeation barrier layer prepared in this embodiment was tested using a homemade bending fatigue testing machine to obtain the life before fracture at room temperature. A 45° bending fatigue test was performed on a QJWQ-6 CNC bending testing machine at a rate of 60 times per minute until the sample fractured, and the bending fatigue life was obtained.

[0051] The hydrogen permeation barrier layer for improving the life of titanium alloy prepared by in-situ oxidation in Example 3 has a bending fatigue test and a bending life of 2.6 x 10 4 , which is 3.88 times the fatigue life of the titanium alloy without a hydrogen permeation barrier (the initial titanium alloy without a hydrogen permeation barrier is 6704 times).

[0052] Example 4

[0053] A method for preparing a hydrogen permeation-resistant protective layer for improving the service life of a titanium alloy, the specific steps are as follows:

[0054] Step 1, mixed gas: turn on the gas source and let oxygen and argon pass through the mixing device in the set ratio to achieve precise mixing. The content of oxygen and argon is: 80% argon and 20% oxygen. Use a sensor to monitor the concentration of the mixed gas. The argon concentration is 99.999% and the oxygen concentration is 99.5%.

[0055] Step 2, titanium alloy selection: The titanium alloy matrix needs to contain aluminum elements. A new metastable β titanium alloy is selected, whose nominal composition is Ti3Al15V3Cr3Sn. The hydrogen content of the titanium alloy before oxidation is less than 5PPm.

[0056] Step 3, preparation of a hydrogen permeation resistance protective layer: the titanium alloy selected in step 2 is ultrasonically cleaned and then loaded into a vacuum furnace. In order to effectively reduce the content of oxygen and water vapor in the furnace, argon gas is first introduced and the vacuum pump is evacuated to 8 Pa. The temperature of the vacuum furnace is then increased to the oxygen permeation temperature of 450°C. After 1.5 hours, the vacuum pump is turned off. Finally, the mixed gas in step 1 is introduced into the vacuum furnace. The vacuum pressure gauge accurately shows that the pressure value inside the system is 0.023 MPa. At this time, the pressure in the vacuum furnace is lower than the standard atmospheric pressure. The oxygen permeation process is carried out for 12 hours to prepare a hydrogen permeation resistance protective layer on the surface of the titanium alloy.

[0057] The titanium alloy with a hydrogen permeation barrier layer prepared in this embodiment was subjected to a hydrogen permeation experiment using an electrochemical workstation. The hydrogen permeation time was 7 days. All electrolytic solutions were 3.5% NaCl aqueous solutions. The negative electrode was the titanium alloy with a hydrogen permeation barrier layer, the positive electrode was pure zinc, and the temperature was room temperature.

[0058] The titanium alloy with the hydrogen permeation barrier layer prepared in this embodiment was tested using a homemade bending fatigue testing machine to obtain the life before fracture at room temperature. A 45° bending fatigue test was performed on a QJWQ-6 CNC bending testing machine at a rate of 60 times per minute until the sample fractured, and the bending fatigue life was obtained.

[0059] In Example 4, the hydrogen permeation barrier layer for improving the life of the titanium alloy is prepared by in-situ oxidation method. Figure 2 As shown in the figure, the hydrogen permeation barrier layer is composed of surface aluminum oxide and internal dioxide layer, and the interface between the two oxide layers and the titanium alloy matrix is ​​clear. After bending fatigue test, the bending life before fracture is 3.6ⅹ10 4 , which is 5.37 times the fatigue life of the titanium alloy without a hydrogen permeation barrier (the initial titanium alloy without a hydrogen permeation barrier is 6704 times).

[0060] Example 5

[0061] A method for preparing a hydrogen permeation-resistant protective layer for improving the service life of a titanium alloy, the specific steps are as follows:

[0062] Step 1, mixed gas: turn on the gas source and let oxygen and argon pass through the mixing device in the set ratio to achieve precise mixing. The content of oxygen and argon is: 85% argon and 15% oxygen. Use a sensor to monitor the concentration of the mixed gas. The argon concentration is 99.999% and the oxygen concentration is 99.5%.

[0063] Step 2, titanium alloy selection: The titanium alloy matrix needs to contain aluminum elements. A new metastable β titanium alloy is selected, whose nominal composition is Ti3Al15V3Cr3Sn. The hydrogen content of the titanium alloy before oxidation is less than 5PPm.

[0064] Step 3, preparation of a hydrogen permeation resistance protective layer: the titanium alloy selected in step 2 is ultrasonically cleaned and then loaded into a vacuum furnace. In order to effectively reduce the content of oxygen and water vapor in the furnace, argon gas is first introduced and the vacuum pump is evacuated to 8 Pa. The temperature of the vacuum furnace is then increased to the oxygen permeation temperature of 450°C. After 1.5 hours, the vacuum pump is turned off. Finally, the mixed gas in step 1 is introduced into the vacuum furnace. The vacuum pressure gauge accurately shows that the pressure value inside the system is 0.023 MPa. At this time, the pressure in the vacuum furnace is lower than the standard atmospheric pressure. The oxygen permeation process is carried out for 24 hours to prepare a hydrogen permeation resistance protective layer on the surface of the titanium alloy.

[0065] The titanium alloy with a hydrogen permeation barrier layer prepared in this embodiment was subjected to a hydrogen permeation experiment using an electrochemical workstation. The hydrogen permeation time was 7 days. All electrolytic solutions were 3.5% NaCl aqueous solutions. The negative electrode was the titanium alloy with a hydrogen permeation barrier layer, the positive electrode was pure zinc, and the temperature was room temperature.

[0066] The titanium alloy with the hydrogen permeation barrier layer prepared in this embodiment was tested using a homemade bending fatigue testing machine to obtain the life before fracture at room temperature. A 45° bending fatigue test was performed on a QJWQ-6 CNC bending testing machine at a rate of 60 times per minute until the sample fractured, and the bending fatigue life was obtained.

[0067] The hydrogen permeation barrier layer for improving the life of titanium alloy prepared by in-situ oxidation in Example 5 has a bending fatigue test and a bending life before fracture of 1.2 x 10 4 , which is 1.79 times the fatigue life of the titanium alloy without a hydrogen permeation barrier (the initial fatigue life of the titanium alloy without a hydrogen permeation barrier is 6704 times).

[0068] Example 6

[0069] A method for preparing a hydrogen permeation-resistant protective layer for improving the service life of a titanium alloy, the specific steps are as follows:

[0070] Step 1, mixed gas: turn on the gas source and let oxygen and argon pass through the mixing device in the set ratio to achieve precise mixing. The content of oxygen and argon is: 95% argon and 5% oxygen. Use a sensor to monitor the concentration of the mixed gas. The argon concentration is 99.999% and the oxygen concentration is 99.5%.

[0071] Step 2, titanium alloy selection: The titanium alloy matrix needs to contain aluminum elements. A new metastable β titanium alloy is selected, whose nominal composition is Ti3Al15V3Cr3Sn. The hydrogen content of the titanium alloy before oxidation is less than 5PPm.

[0072] Step 3, preparation of a hydrogen permeation resistance protective layer: the titanium alloy selected in step 2 is ultrasonically cleaned and then loaded into a vacuum furnace. In order to effectively reduce the content of oxygen and water vapor in the furnace, argon gas is first introduced and the vacuum pump is evacuated to 8 Pa. The temperature of the vacuum furnace is then increased to the oxygen permeation temperature of 600°C. After 1.5 hours, the vacuum pump is turned off. Finally, the mixed gas in step 1 is introduced into the vacuum furnace. The vacuum pressure gauge accurately shows that the pressure value inside the system is 0.023 MPa. At this time, the pressure in the vacuum furnace is lower than the standard atmospheric pressure. The oxygen permeation process is carried out for 1 hour to prepare a hydrogen permeation resistance protective layer on the surface of the titanium alloy.

[0073] The titanium alloy with a hydrogen permeation barrier layer prepared in this embodiment was subjected to a hydrogen permeation experiment using an electrochemical workstation. The hydrogen permeation time was 7 days. All electrolytic solutions were 3.5% NaCl aqueous solutions. The negative electrode was the titanium alloy with a hydrogen permeation barrier layer, the positive electrode was pure zinc, and the temperature was room temperature.

[0074] The titanium alloy with the hydrogen permeation barrier layer prepared in this embodiment was tested using a homemade bending fatigue testing machine to obtain the life before fracture at room temperature. A 45° bending fatigue test was performed on a QJWQ-6 CNC bending testing machine at a rate of 60 times per minute until the sample fractured, and the bending fatigue life was obtained.

[0075] The hydrogen permeation barrier layer for improving the life of titanium alloy prepared by in-situ oxidation in Example 6 has a bending fatigue test and a bending life before fracture of 2.7 x 10 4 , which is 4.02 times the fatigue life of the titanium alloy without a hydrogen permeation barrier (the initial titanium alloy without a hydrogen permeation barrier is 6704 times).

[0076] The above description of the present invention is only a partial embodiment, but the present invention is not limited to the above examples. The above embodiments are illustrative and not restrictive. All specific extensions of the materials and methods of the present invention, without departing from the scope of protection of the present invention and the claims, are within the scope of protection of the present invention.

Claims

1. A method for preparing a hydrogen permeation barrier layer for improving the service life of a titanium alloy, characterized in that: The specific steps include: Step 1, mixed gas: turn on the gas source, let oxygen and argon pass through the mixing device in the set ratio to achieve precise mixing, and use the sensor to monitor the concentration of the mixed gas. The argon concentration is 99.999% and the oxygen concentration is 99.5%; Step 2, titanium alloy selection: the titanium alloy matrix needs to contain aluminum elements, and a new metastable β titanium alloy is selected, whose nominal composition is Ti3Al15V3Cr3Sn; Step 3, preparation of a hydrogen permeation resistance protective layer: the titanium alloy selected in step 2 is ultrasonically cleaned and then loaded into a vacuum furnace. First, argon gas is introduced and the vacuum pump is evacuated to 8Pa. Then the temperature of the vacuum furnace is increased to the oxygen permeation temperature. After 1.5 hours, the vacuum pump is turned off. Finally, the mixed gas in step 1 is introduced into the vacuum furnace. The pressure in the vacuum furnace is 0.023MPa. At this time, the pressure in the vacuum furnace is lower than the standard atmospheric pressure. The oxygen permeation process is carried out to prepare a hydrogen permeation resistance protective layer on the surface of the titanium alloy.

2. The method for preparing a hydrogen permeation barrier layer for improving the service life of a titanium alloy according to claim 1, characterized in that: In step 1, the contents of oxygen and argon are: 80%-95% of argon and 5%-20% of oxygen.

3. The method for preparing a hydrogen permeation barrier layer for improving the service life of a titanium alloy according to claim 1, characterized in that: In step 2, the hydrogen content of the titanium alloy is less than 5 PPm.

4. A method for preparing a hydrogen permeation barrier layer for improving the service life of a titanium alloy according to claim 1, characterized in that: In step 3, the oxygenation temperature is 300-600° C., and the oxygenation process lasts 1-24 hours.

5. The hydrogen permeation barrier layer prepared by the method for preparing a hydrogen permeation barrier layer for improving the service life of a titanium alloy according to any one of claims 1 to 4 is characterized in that: The outer layer of the hydrogen permeation barrier is Al2O3, and the inner layer is TiO2. The Ti and Al elements in the hydrogen permeation barrier come from the inside of the titanium alloy, and the O element comes from the mixed gas of oxygen and argon in the vacuum furnace.

Citation Information

Patent Citations

  • In-situ synthesized TiC particle-reinforced titanium aluminium alloy material and preparation method thereof

    CN102876919A

  • Preparation method for hydrogen-resistance permeation layer on surface of metal hydride

    CN107043906A

  • Preparation method of titanium alloy surface insulation hardened film layer and titanium alloy

    CN115710685A

  • Hydrogen permeation-resistant composite vitreous barrier layer for stainless steel substrate and preparation method and application of hydrogen permeation-resistant composite vitreous barrier layer

    CN116200743A

  • High-bonding-strength in-situ oxidation coating on surface of titanium product and preparation method

    CN118792713A

Cited By

  • Ni-Zn-P-ZnO composite hydrogen-resistant coating and preparation method thereof

    CN121826827A